Evolution of universal review and disclosure of MRI reports to research participants - Shoemaker, Jody M. (Brain Behav, 2016)
BACKGROUND: Although incidental findings (IF) are commonly encountered in neuroimaging research, there is no consensus regarding what to do with them. Whether researchers are obligated to review scans for IF, or if such findings should be disclosed to research participants at all, is controversial. Objective data are required to inform reasonable research policy; unfortunately, such data are lacking in the published literature. This manuscript summarizes the development of a radiology review and disclosure system in place at a neuroimaging research institute and its impact on key stakeholders. METHODS: The evolution of a universal radiology review system is described, from inception to its current status. Financial information is reviewed, and stakeholder impact is characterized through surveys and interviews. RESULTS: Consistent with prior reports, 34% of research participants had an incidental finding identified, of which 2.5% required urgent medical attention. A total of 87% of research participants wanted their magnetic resonance imaging (MRI) results regardless of clinical significance and 91% considered getting an MRI report a benefit of study participation. A total of 63% of participants who were encouraged to see a doctor about their incidental finding actually followed up with a physician. Reasons provided for not following‐up included already knowing the finding existed (14%), not being able to afford seeing a physician (29%), or being reassured after speaking with the institute's Medical Director (43%). Of those participants who followed the recommendation to see a physician, nine (38%) required further diagnostic testing. No participants, including those who pursued further testing, regretted receiving their MRI report, although two participants expressed concern about the excessive personal cost. The current cost of the radiology review system is about $23 per scan. CONCLUSIONS: It is possible to provide universal radiology review of research scans through a system that is cost‐effective, minimizes investigator burden, and does not overwhelm local healthcare resources.